BANDUNG FASHION HUB SEBAGAI RUANG INTERAKSI DAN REKREASI DENGAN PENDEKATAN DESAIN EKSPRESIF DI KOTA BANDUNG - Annisa Fadhilla Jasmine; MDE Purnomo; Hari Yuliarso (ARSITEKTURA, 2016)
Today’s fashion is an important part of the lifestyle and influence in many aspects of life including influential in global economic that the development should be considered. Bandung as a creative city supported by enterprising creative industries and communities is a suitable habitat in the development of the fashion mode that has significant impact on the development of the creative economy in the city of Bandung. Based on the Government Work Report Bandung (LKPJ AMJ) in 2012, the growth of creative industries has decreased. Fashion needs to be developed starting from human resources, the manufacturing process of mode, distribution of works / fashion products, activities in the networking community, the container activities of urban communities to engage in communal and urban public recreation in the creative space. Therefore, the existence of Bandung Fashion Hub as a center of fashion in Bandung is indispensable. Of these issues, the design problem is to what extent the expression of space and forms that can be imaged expression of fashion stakeholder interaction and how to express creatively through fashion symbol of the city which can be a recreational space in the city of Bandung. The method used is a method of planning and designing architecture namely by processing the data and information (concept of) for creating design concept (concept for design) through the process of programming, design criteria and performance of a design concept. Expressive design approach by using the meaning of the symbol, the idea of space, form that expose the material so that it can express the character of fashion events and characters of Bandung as a creative city. Therefore the design of Bandung Fashion Hub aims to facilitate all activities related to the character of the activities of fashion stakeholders including forecasting activities, show off, market and shop. Fashion hub as a place to meet and communicate between communities and the media as well as with fashion activists in general and also as a place of education and information (forecasting), promotion (market), exhibitions (show off) and recreation for the community so as to enhance the growth of creative industries in Bandung. Keywords: Bandung, Creative City, Creative Industry, Expressive Design, Fashion, Hub